Transparent Sonic Sculptures in Site-Specific Intermedia Music - Fujak, Július (Res Facta Nova, 2022)
The paper deals in the first part with the centripetal juxtaposition of Marcel Duchamp’s Sculpture Musicale and John Cage’s 4’33”. Both pieces became the starting points of the author´s creation of acousmatic comprovised music saving/transforming unique soundscapes (mostly) in Slovakia. The sounds of specific environments (with semantic social meanings) as a kind of unique musical-sonic sculptures were involved in his musical artistic projects: e. g. Animation of Silence (in Music) of Puppets (2000), or Nitrian Atlantises (2013) dedicated to the part of the pre-ancient history of Nitra as well as to semantic parallels of this period in the contemporary life of the city. Melancholy (2017), co-created with the fine artist Slavomír Zombek and the poet Peter Milčák, has changed the site of a desolate cowhouse near Levoča to the site-specific gallery/concert hall of sounding events. Sonic Sculpture of Bin (2018) inspired by Duchamp’s idea mentioned above was realized in a deserted refinery in Rimavská Sobota as site-specific sonic-musical piece, as well as other transparent sonic sculptures Cockroach Lure (2019) with intermedia artist Petr Nikl, and two pieces, La Mer (2021/2022) and ÚÚÚ-FFF-ÓÓÓ (2021), dedicated to two great Slovak conceptual intermedia artists, Milan Adamčiak and Július Koller. In the final comment, the author writes about the phenomena of sonic photography – related to the ideas of Roland Barthes’ La Chambre Claire – which can be appropriated as an organic part of transparent sonic-musical sculpture.